2014
DOI: 10.1073/pnas.1323985111
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 9 signaling acts on multiple elements of the germinal center to enhance antibody responses

Abstract: Recent studies have demonstrated important roles of nucleic acidsensing Toll-like receptors (TLRs) in promoting protective antibody responses against several viruses. To dissect how recognition of nucleic acids by TLRs enhances germinal center (GC) responses, mice selectively deleted for myeloid differentiation primaryresponse protein 88 (MyD88) in B cells or dendritic cells (DCs) were immunized with a haptenated protein antigen bound to a TLR9 ligand. TLR9 signaling in DCs led to greater numbers of follicular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 75 publications
7
87
0
Order By: Relevance
“…These results are concordant with the recent reports in mouse models that CpG-DNA could increase T FH and B cell responses (Chakarov and Fazilleau, 2014;Mastelic et al, 2012;Rookhuizen and DeFranco, 2014).…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 93%
“…These results are concordant with the recent reports in mouse models that CpG-DNA could increase T FH and B cell responses (Chakarov and Fazilleau, 2014;Mastelic et al, 2012;Rookhuizen and DeFranco, 2014).…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 93%
“…Previous publications have reported a correlation between the magnitude of GC B cells and T FH cells in response to increasing amount of Ag or to TLR agonists in the adjuvant formulation (39,42,43); in addition, a recent study from Siegrist and colleagues (44) has shown that MF59 promotes potent T FH and GC B cell responses in adult mice, whereas younger infant mice, which develop only few functional T FH cells, have poor GC and Ab responses. In the present work, we show higher frequencies of T FH cells in proximal-draining LNs of mice that received the MF59 formulation compared with the alum group, hence confirming the importance of the adjuvant in shaping T FH cell responses and providing a possible explanation to the sustained Ag-specific GC B cell responses observed with MF59 formulation.…”
Section: Discussionmentioning
confidence: 97%
“…Along this line, Karnowski et al (2012) have recently reported that Pou2af1 −/− CD4 + T cells are not impaired in their ability to differentiate into Tfh cells during influenza infection in mice reconstituted with wild‐type B cells. Viral infections, however, elicit strong Toll‐like receptor signals not only in DCs and B cells, but also in CD4 + T cells that, depending on the pathogenic stimulus and the anatomic compartment, promote the generation of Tfh cells and adaptive immune responses (Hou et al , 2011; Rookhuizen & Defranco, 2014; Kubinak et al , 2015). Based on our observation that Bob can be decisive for CD4 + T‐cell differentiation (Brunner et al , 2007), we analyzed Pou2af1 +/+ : Pou2af1 −/− mixed bone marrow chimeras to determine whether the effects of Bob1‐deficiency on Tfh cell differentiation are CD4 + T cell‐intrinsic or secondary to defects in the B‐cell compartment of Pou2af1 −/− mice.…”
Section: Discussionmentioning
confidence: 99%